The Implementation of Healthy Household Practices on Non-Smoking Indicators at the Pakuan Baru Community Health Center in 2024Implementation of Healthy Household Practices on Non-Smoking Indicators at the Pakuan Baru Community Health Center in 2024 - Nadhira Beninda; Puspita Sari; Rizhalia Wardiah; Muhammad Rifqi Azhary; M. Ridwan; Andree Aulia Rahmat (CV. AFDIFAL MAJU BERKAH, 2025)
The Clean and Healthy Living Behavior Program (PHBS) is a crucial government effort designed to enhance public health by promoting behavioral change. A key indicator of this program is not smoking indoors. Data from the Pakuan Baru Community Health Center in Jambi City in 2023 reveals that achievement of this indicator remains alarmingly low, at 40.95%, significantly below the national target of 72%. This substantial gap underscores the urgent necessity for an in-depth evaluation of the PHBS program's implementation at the household level. This investigation utilized a qualitative method with a descriptive approach. Data collection was comprehensive, involving in-depth interviews, Focus Group Discussions (FGD), field observations, and documentation review. Informants included the Head of the Pakuan Baru Community Health Center, health promotion educators, and community members within the center's working area. The study findings indicate that the PHBS program's implementation has not been optimal. The primary obstacles identified stem from limited human resources and funding, coupled with a mismatch between central and regional indicators. Despite these challenges, the research noted positive behavioral changes in some families who have successfully adopted the habit of not smoking indoors. The strategies employed for the PHBS program on the smoke-free indoors indicator have been diverse but consistently face hurdles related to local culture and long-standing community habits. While initial behavioral shifts are evident in certain households, a more targeted and specific approach is critical to amplify the program’s effectiveness. Future interventions must prioritize improved education, stronger cross-sector support, and the optimization of health cadres’ roles as pivotal factors in successfully achieving smoke-free households.